Synthesis of Hydrazinylpyridines via Nucleophilic Aromatic Substitution and Further Transformation to Bicyclo[2.2.2]octenes Fused with Two N-Aminosuccinimide Moieties - Ekar, Jernej; Kranjc, Krištof (Synthesis, 2020)
Efficient and reliable synthesis of substituted hydrazinylpyridines in thick-wall ACE tubes via nucleophilic substitution of a chlorine substituent in different chloropyridines is presented. Hydrazine hydrate and alkylhydrazines were used as nucleophiles and simple alcohols and diethyl ether were the only organic solvents necessary, making the process environmentally and user friendly, potentially reaching 100% atomic efficiency. In the next step, transformations of succinic anhydride moieties fused to the bicyclo[2.2.2]octene framework into succinimide moieties via nucleophilic substitution of oxygens were conducted. As nucleophiles two of the synthesized hydrazinylpyridines (2-hydrazinyl-3-nitropyridine and 2-hydrazinyl-5-nitropyridine) and also hydrazine hydrate, phenylhydrazine, and 4-nitrophenylhydrazine were used. Reactions were again carried out in ACE tubes and only simple alcohols, diethyl ether, and acetone were needed as solvents. One of the prepared bicyclo[2.2.2]octene adducts displayed water solubility thus being a promising candidate for future studies as a novel bidentate ligand for various metal cations in aqueous solutions or acting as an unprecedented halogen bond acceptor.
Keywords: green chemistry; chloropyridine; bicyclo[2.2.2]octene; water-soluble ligand; succinimide; nucleophilic substitution